THE IMPACT OF RUSSIA-UKRAINE WAR ON ENERGY POLICY MANEUVERS TO STRENGTHEN ENERGY SECURITY AND CYBERSECURITY IN INDONESIA - Rizaldi, Bobby Adhityo; Idris, Abdi Manab; Nurbaiti, Nurbaiti (Journal of Terrorism Studies, 2023)
The war between Russia and Ukraine is highly discussed in global geopolitics and geostrategy. The strategy of attacking Russia directly at the point of a vital national object, namely the power plant, which was preceded by a cyber attack at the Nuclear Power Plant in Chornobyl, followed by a conventional physical attack from the air, resulted in an energy crisis in Ukraine. The resulting war affects many sectors, such as the energy sector, food, and supply chains, especially (at the end of 2021) before the war. WTI oil price was only around 75$/barrel, but when the war broke out, the price increased to 130$ (in August: 93$). It is estimated that oil prices will not fall significantly as long as the war is not over. The direct impact of war disrupts global energy security. This research uses a qualitative study based on the theory of incremental policy from several experts who support new policies quickly and national defense and energy security. Based on the incremental policy, policies that support the strengthening of cybersecurity will be produced, ranging from cryptographic policies to the potential for highly advanced energy sector blockchains.